Implementation of Heavy Damaged Regional Property Disposal in Mataram City Government - Martina, Putu Wawan; Herwanti, Titiek; Hermanto, Hermanto (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2018)
Abstract: Implementation of Heavy Damaged Regional Property Disposal in Mataram City Government. This study aimed to determine and analyse the disposal process of Regional Property or known as Barang Milik Daerah (BMD), which were heavily damaged, in Mataram City Government in accordance to Ministry of Home Affairs Regulation Number 19 Year 2016. The new regulation regarding the disposal process of BMD changed the required procedures, compared to the previous regulations. This study found that the disposal process of heavily damaged BMD in the Mataram City Government was centered on the BPKAD Kota Mataram as the leading sector of BMD management. The main obstacle of disposal process is incomplete documents and physical vagueness of goods proposed to be disposed. These problems were caused by several things; the grant process in the past which were not accompanied by proper documents, unreliable supervision for heavily damaged BMD, frequent changes of SKPD office site, unskilled human resources, and the lack of a Standard Operational Procedure (SOP) for disposal process. Keywords: Heavy Damaged Regional Property, Disposal, Regional Property ManagementAbstrak: Implementasi Penghapusan Barang Milik Daerah Rusak Berat Pada Pemerintah Kota Mataram. Riset ini memiliki tujuan untuk mengetahui implementasi penghapusan BMD rusak berat pada Pemerintah Kota Mataram berdasarkan Permendagri No. 19 Tahun 2016. Proses penghapusan BMD berdasarkan Permendagri No. 19 Tahun 2016 mengalami perubahan mekanisme jika dibandingkan dengan aturan sebelumnya. Berdasarkan hasil riset menunjukkan bahwa proses penghapusan BMD rusak berat pada Pemerintah Kota Mataram pelaksanaannya masih dipusatkan pada Badan Pengelolaan Keuangan dan Aset (BPKAD) Kota Mataram selaku leading sector pengelolaan BMD. Kendala utama yang menjadi penghambat adalah ketidaklengkapan dokumen serta ketidakjelasan fisik barang yang diusulkan untuk dihapuskan. Hal tersebut disebabkan karena beberapa hal yaitu proses hibah di masa lalu yang tidak disertai dokumen, pengawasan yang belum maksimal terhadap BMD rusak berat, seringnya terjadi perpindahan kantor Satuan Kerja Perangkat Daerah (SKPD), Sumber Daya Manusia (SDM) yang belum memadai, serta tidak adanya Standar Operasional Prosedur (SOP) tentang penghapusan BMD. Kata kunci: BMD Rusak Berat, Penghapusan, Pengelolaan BMD